Hybrid approach with laparoscopic wall‐inversion surgery and single‐incision intragastric surgery for intraluminal gastrointestinal stromal tumor: A case report. Issue 4 (16th February 2021) - Kusunoki, Chikako; Hamakawa, Takuya; Nishikawa, Kazuhiro; Sato, Hiromichi; Imamura, Sayumi; Miyahara, Satoru; Sakano, Yu; Miyazaki, Hazuki; Seto, Hiroto; Ueda, Ryuta; Toshiyama, Reishi; Miyo, Masaaki; et al.
Abstract: Laparoscopic wedge resection (LWR) for intraluminal gastrointestinal stromal tumor (GIST) leads to excessive resection of normal gastric wall. We report a case of GIST around the cardia successfully treated with full‐thickness partial resection using a hybrid approach of laparoscopic surgery and single‐incision intragastric surgery (SIIGS). A 69‐year‐old woman had a 5 cm intraluminal GIST at the posterior wall around the cardia. Submucosal injection of glycerin and indigo carmine was performed with transoral endoscopy. Circumferential seromuscular incision followed by placement of seromuscular sutures to invert the lesion into the stomach was performed under laparoscopy. By SIIGS, resection of the inverted mucosa and retrieval of the tumor were completed. A hybrid approach consisting of laparoscopic wall‐inversion surgery and SIIGS was useful for intraluminal GIST and may expand the indications for laparoscopic wall‐inversion surgery by removing size limitations.